Economic Development and the Division of Production between Households and Markets - Locay, Luis (Journal of Political Economy, 1990)
A model is presented in which scale economies give market production a cost advantage over household production, but in which market production is limited by the extent of the market. The production process is viewed as a series of stages, each further refining and specializing the product of the previous stage. As processing proceeds, the number of intermediate goods increases and markets thin out. Firms specialize in the early stages of production and house-holds in the later stages. As an economy grows, production shifts out of households and into the market. Several other changes associated with economic development are also accounted for.